Strategi Manajemen Humas dalam Meningkatkan Citra Sekolah Di SMPN 16 Surabaya - Ita Sri; Lailatul Fitriyah; Dwi Cahyo Kurniawan; Ima Widiyanah; Karwanto Karwanto (Jurnal Penelitian, 2025)
To improve the image of the school, the role of the community and society is very important in achieving the school's programme. In addition, implementing public relations management in educational institutions serves as a communication bridge or an extension of information in building a positive image of the school. The research conducted at SMPN 16 Surabaya aims to explain the public relations strategies used to build the image of SMPN 16 Surabaya as a school worthy of being a reference for parents amid technological developments to become one of the educational institutions for their children to attend. Data for this descriptive qualitative research was collected using interview techniques, observation, and document analysis. The research targets were the community of SMP Negeri 16 Surabaya (accredited A, score 92), including public relations, the principal, teachers, and students